2000
DOI: 10.1021/jo991067b
|View full text |Cite
|
Sign up to set email alerts
|

Facile Ring-Opening Reactions of Phthalimides as a New Strategy to Synthesize Amide-Functionalized Phosphonates, Primary Phosphines, and Bisphosphines

Abstract: The nucleophile-assisted ring-opening reaction of phthalimides 1 has been studied. The reaction of phthalimides 1 with 0.5 equiv of hydrazine produced the novel bisphosphonates 2 in near quantitative yields whereas with 10-fold excess of hydrazine, diethyl aminoalkylphosphonates 3 was formed in 75% yields. The reaction of phthalimide 1b with 3-(aminopropyl)phosphine resulted in a novel compound 4a containing a PIII hydride and a PV phosphonate within the same molecule. In addition, the reaction of 1b with 2-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 36 publications
(48 reference statements)
0
45
0
1
Order By: Relevance
“…Griffiths [25] proposed the same methodology in the course of a tetramethylester bisphosphonate preparation, but deprotection of the phthalimides in refluxing HBr also cleaved all the phosphonic esters. Nevertheless, Gali et al [26] showed that on diethyl alkylphthalimide phosphonates, the use of excess hydrazine can selectively deprotect the amine function without any ester cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…Griffiths [25] proposed the same methodology in the course of a tetramethylester bisphosphonate preparation, but deprotection of the phthalimides in refluxing HBr also cleaved all the phosphonic esters. Nevertheless, Gali et al [26] showed that on diethyl alkylphthalimide phosphonates, the use of excess hydrazine can selectively deprotect the amine function without any ester cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…The nucleophile assisted ring-opening reactions of phosphonate bearing phthalimide 13 has been utilized in the synthesis of mixed primary phosphinephosphonate and aromatic amide functionalized primary bisphosphines as outlined in Scheme 6 [50].…”
Section: Mixed Phosphonate and Aromatic Amide Functionalized Primary mentioning
confidence: 99%
“…For example, the interaction of aminopropyl phosphine (3) with the phthalimide 13 produced rare example of a phosphonate functionalized primary phosphine 14 in excellent yields (Scheme 6) [50]. The corresponding reaction of the phthalimide phosphonate 13 with 0.5 equivalent of hydrazine resulted in the bisphosphonate species 15 which upon further reduction with LiAlH 4 produced the primary bisphosphine 16 functionalized with aromatic amides.…”
Section: Mixed Phosphonate and Aromatic Amide Functionalized Primary mentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions with carbonyl groups, alkyl and aryl halides, halogens, alkali metals, and Lewis acids are well known and provide many possibilities to produce functionalized, even chiral-phosphorus containing secondary or tertiary phosphines. [9] However, one of the most convenient methods is deprotonation of the primary phosphine by using organometallic compounds of the alkali metals as strong bases. Twofold deprotonations are also possible by this method.…”
mentioning
confidence: 99%